Experiences and conclusions from the military use of the Great Masurian Lakes area in the 20th century - Łach, Wiesław Bolesław (Armia kontra natura, 2020)
In the eastern part of the Warmian-Masurian Voivodeship, lies the Land of the Great Masurian Lakes. The line of these lakes during the First World War crossed the roads leading from the east into the German Reich, forcing the Russian army to circumvent it in 1914 and contributed to their defeat. In 1915, this entire natural defensive line was modernized and was ready for combat. However, in the interwar period it was additionally strengthened with a new fortification system. In 1940, the work started, in addition to expanding the existing fortification system, included the construction of a group of command posts for central state and military authorities (including headquarters for Adolf Hitler near Kętrzyn). In 1944, Germany prepared intensively for defense, expanding its fortification system, hoping that Masurian lakes would become the axis of defense. However, the nature of the combat operations in 1945 differed fundamentally from the 1914 fights. The Red Army broke the fortifications of the German defensive lines by maneuvering and destroying the areas of resistance. After the World War II, the lake area was within the Polish state. The army took over Gὅring’s headquarters in Broad Bor creating ammunition stores. The training ground in Orzysz and barracks facilities were used to locate military units in Węgorzewo and Giżycko. In the 1960s, using the natural conditions of the lakes, the 32nd Brigade of operational-tactical missiles was located in Orzysz. The close location of the Polish border with Russia in the 1990s meant that a German inventory of German fortifications and military facilities was carried out, and the Great Masurian Lakes are treated as an axis of possible tactical operations in northern Poland. The character of stationed units, which are operational in nature, has changed, and the training ground in Orzysz has become the base of allied forces.